2012
DOI: 10.1902/jop.2011.110327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non‐Surgical Periodontal Treatment on Clinical Response, Serum Inflammatory Parameters, and Metabolic Control in Patients With Type 2 Diabetes: A Randomized Study

Abstract: Non-surgical periodontal treatment can effectively improve periodontal and circulating inflammatory status. Despite a lack of strong evidence, trends in some results support improved glycemic control after periodontal treatment in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
196
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(218 citation statements)
references
References 42 publications
14
196
1
7
Order By: Relevance
“…These results are consistent with those from previous studies in which the effect of FM-SRP, subgingival curettage, and tooth cleaning treatments on glycaemic control has been evaluated [26,[29][30][31][32].…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with those from previous studies in which the effect of FM-SRP, subgingival curettage, and tooth cleaning treatments on glycaemic control has been evaluated [26,[29][30][31][32].…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with other three clinical studies (Correa et al 2010, Duarte et al 2010, Sun et al 2011) describing the effect of periodontal therapy in individuals suffering also from other co-morbidities including diabetes. An equal number of trials failed to show a statistically significant effect of periodontal therapy on TNF-a (Ide et al 2003, Lalla et al 2007, Kallio et al 2008, Buhlin et al 2009, Fentoglu et al 2011, Chen et al 2012. Lastly, Fokkema et al (2003) investigated the long-term effect of full-mouth tooth extraction therapy on the responsiveness of peripheral blood monocytes in a single subject with generalized terminal adult periodontitis reporting no changes in TNF-a release before and after therapy.…”
Section: Cytokinesmentioning
confidence: 99%
“…15,16 The role of periodontal treatment in serum inflammatory markers is somewhat conflicting, possibly because of differences in periodontal therapy protocols (time of follow-up and use of local/systemic antimicrobials). Some studies have shown considerable changes in the serum levels of IL-6 and TNF-α, 17,18 whereas others have disclosed no significant changes in TNF-α, 19 20 and IL-8. 21 To the best of our knowledge, there is no information regarding the effect of strict supragingival biofilm control on inflammatory burden.…”
Section: Introductionmentioning
confidence: 99%